Asupan Lemak dan Aktifitas Fisik pada Siswa SMP dengan Status Gizi Gemuk - Listianasari, Yanita; Putra, Ahmad Faris Eka (Nutriology : Jurnal Pangan, Gizi, Kesehatan, 2023)
Abstract Overweight and obesity are abnormal conditions or the occurrence of excess fat in adipose tissue and pose a risk of damaging health. In Indonesian, the prevalence of obesity at ages 5 – 12 years are 10,8% and obesity are 8,8%. The prevalence of obesity at the age of 13 – 15 years are 8,3% and obesity are 2,5%. Overweight and obesity can be caused by indirect factors and direct factors. Indirect factors are gender, genetics, age, social environment. Direct factors are food intake and physical activity. The food intake that contributes the greatest energy comes from carbohydrates and fat. This research was conducted to determine fat intake and physical activity in junior high school students who were overweight and obese in Tasikmalaya City. This research is descriptive research conducted from February to April 2023. Data were collected using anthropometric measurements to determine the nutritional status of respondents, interviews using the SQ-FFQ and IPAQ formulas to determine fat intake and physical activity. Data collection used a total sampling technique of 20 respondents. The results of the study showed that some teenagers with a nutritional status of overweight and obesity at junior hight school/ equivalent level experienced problems with food intake and a small percentage experienced problems with physical activity. The conclusion is that overweight and or obese teenagers at junior high school/ equivalent level experience problems with fat intake of 95% and light physical activity o2 20%, moderate physical activity of 75%. Keywords: obesity, teenagers, fat intake, physical activity